2018
DOI: 10.3390/children5100140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Physical Activities with Mathematics on Objectively Assessed Physical Activity

Abstract: Background: One of the promising strategies for increasing physical activity (PA) at school is to integrate it with academic learning. The purposes of this study were: (a) to examine differences in objectively measured PA levels between integrated PA with mathematics and traditional lessons, and (b) to evaluate the PA levels of different integrated PAs. Methods: Seventy-seven 4th grade students (41 males) were included in an intervention (Move for Thought program: M4T) group (n = 46) that utilized PA integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…They contributed to a reduction in physical sedentarism and to an increase in the levels of MVPA in accordance with stipulated health advice. The results were consistent with the higher effects of MVPA reported by previous research into ABs that also focused on the school day [13,[35][36][37]. It was observed that the participating school children were sedentary for an average of 82.54% of the time in the case of the control group and 71.99% for the experimental group.…”
Section: Discussionsupporting
confidence: 90%
“…They contributed to a reduction in physical sedentarism and to an increase in the levels of MVPA in accordance with stipulated health advice. The results were consistent with the higher effects of MVPA reported by previous research into ABs that also focused on the school day [13,[35][36][37]. It was observed that the participating school children were sedentary for an average of 82.54% of the time in the case of the control group and 71.99% for the experimental group.…”
Section: Discussionsupporting
confidence: 90%
“…This duration has been shown to be the most common in classroom‐based physical activity research 8 . This present study extends current research of the ‘Move for Thought’ (M4T) elementary programme that has been found to increase children's math performance 18 and physical activity levels, 19 compared to traditional instruction.…”
Section: Introductionsupporting
confidence: 74%
“…Each activity was designed to be repeated multiple times for a period of approximately 10–12 min. This duration has been found to be feasible and effective 7,19 …”
Section: Methodsmentioning
confidence: 99%
“…Some authors consider ABs to be an effective approach to promote PA with the final aim of improving students’ health since school time represents an ideal setting for such purposes [ 6 ]. There is evidence confirming that school-based PA interventions increase students’ PA levels [ 7 , 8 ]. In fact, the scientific literature suggests that the brain learns better when active methodologies (active role of students) are implemented instead of passive methodologies or traditional lessons [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is sufficient evidence to suggest that ABs improve cognition, especially attention [ 20 , 21 , 22 ]. Furthermore, previous evidence has shown that ABs can improve students’ attention [ 7 , 8 , 23 ]. However, results are still heterogeneous [ 2 ] and require further confirmation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%